Portable Altars - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
In a recent book on ancient rituals (Abusch and Schwemer 2016), some passages concern ‘portable altars’. For example : ‘you sweep the g(round), you sprinkle pure water, you SET UP TWO PORTABLE ALTARS (before Sîn and Shamash)’ (Abusch and Schwemer 2016: 291, text 8.36, l.4)